The clash of civilizations and the remaking of world order - Huntington, Samuel P. (New York : Simon & Schuster, 1996)
In the summer of 1993 Foreign Affairs published an article entitled "The Clash of Civilizations?" by Samuel Huntington. No article, according to the editors of that distinguished journal, has generated more discussion since George Kennan's "X" article on containment in the 1940s. Now, Mr. Huntington expands on his article, explores further the issues he raised then, and develops many new penetrating and controversial analyses.
In the article, he posed the question whether conflicts between civilizations would dominate the future of world politics. In the book, he gives his answer, showing not only how clashes between civilizations are the greatest threat to world peace but also how an international order based on civilizations is the best safeguard against war.
Keywords: World politics -- 1989-; Post-communism.; Civilization, Modern -- 1950-